Effect of probiotics on clinical and immune parameters in enthesitis-related arthritis category of juvenile idiopathic arthritis. (19th August 2016) - Shukla, A; Gaur, P; Aggarwal, A
Summary: Gut microflora and dysbiosis as an environmental factor has been linked to the pathogenesis of enthesitis-related arthritis (JIA-ERA); thus, we performed a proof-of-concept study of probiotics to modulate the gut-flora and study the effects on immune and clinical parameters of children having JIA-ERA. Forty-six children with active JIA-ERA were randomized to placebo or probiotic therapy along with non-steroidal anti-inflammatory drugs (NSAIDs) for 12 weeks. Patients were assessed using a six-point composite disease activity index (mJSpADA) based on morning stiffness, joint count, enthesitis count, sacroiliitis/inflammatory back pain, uveitis and erythrocyte sedimentation rate/C-reactive protein (ESR/CRP). Frequencies of T helper type 1 (Th1), Th2, Th17 and regulatory T cells in blood were measured using flow cytometry. Serum cytokines interferon (IFN)-γ, interleukin (IL)−4, IL-17, IL-10, tumour necrosis factor (TNF)-α and IL-6 were measured by cytokine bead array using flow cytometer. The average age of 46 children (44 boys) was 15 ± 2.5 years and duration of disease was 3.5 ± 3 years. There was no significant difference in improvement in mJSpADA between the two groups ( P = 0·16). Serum IL-6 levels showed a decrease ( P < 0·05) in the probiotic-group. Th2 cell frequency ( P < 0·05) and serum IL-10 levels ( P < 0·01) showed an increase in the placebo group, but again the probiotic use did not show a significant change in immune parameters when compared to the placebo. Adverse effects among the probiotic and placebo groups were diarrhea (36 versus 45%), abdominal pain (9 versus 20%), minor infections (4·5 versus 20%) and flatulence (23 versus 15%), respectively. Thus, we can conclude that probiotic therapy in JIA-ERA children is well tolerated, but failed to show any significant immune or clinical effects over NSAID therapy.